Working-from-home (WFH) practice for urban poor responding to pandemic situation - Na’asah, Nasrudin; Yusfida Ayu, Abdullah; Hamizah, Yakob; Azren, Hassan; Zaharah, Mohd Yusoff; Syafiee, Shuid; Nina Suhaity, Azmi (Malaysian Institute of Planners, 2022)
The situation where one can practise working from home is not easy for some people in Malaysia, especially those with limited space at home. Working from home (WFH), on the other hand, needs to be rethought and thoroughly examined for individuals in the bottom 40 percent (B40) for a variety of reasons. A total of 144 samples from low-income households in Shah Alam responded to the structured questionnaire. The questionnaire focuses on two main investigations: (1) the WFH conditions in terms of space and environment among the B40; and (2) how they manage WFH distractions in connection to the house space and environment. According to survey results, most respondents prefer working in a bedroom or living room since it is a more pleasant environment. The availability of electrical plugs, internet access, and adequate ventilation are further considerations that influence their choice of workspace. The survey’s findings indicated that the lack of a comfortable workspace made the majority of respondents unhappy about practising WFH. The majority of responders suggested that future bedrooms be larger to guarantee that those practising WFH are comfortable. The results of this study are expected to enhance the planning and design of residential living space and pave the way for future low-cost housing development that places greater emphasis on the well-being of the urban poor.